Ligand and Anion Co‐Leaching Induced Complete Reconstruction of Polyoxomolybdate‐Organic Complex Oxygen‐Evolving Pre‐Catalysts. (29th May 2021) - Liu, Xiong; Xia, Fanjie; Guo, Ruiting; Huang, Meng; Meng, Jiashen; Wu, Jinsong; Mai, Liqiang
Abstract: The coordination compounds in the oxygen evolution reaction (OER) have been researched extensively. However, their poor durability (mostly < 100 h) and controversial reconstruction mechanism restrict their practical applications. Herein, a new‐type polyoxomolybdate‐organic complex (POMo) via wet‐chemistry synthesis with fixed coordination between metal centers (Ni 2+ and [Mo8 O26 ] 4− ) and 2‐Methylimidazole ligand is introduced. After introducing iron, a series of Fe‐doped Ni‐POMo with porous and amorphous structures are fabricated. These features accelerate the diffusion‐leaching processes of ligands and anions, resulting in rapid and complete phase reconstruction during alkaline OER. As a result, nickel‐iron (oxy)hydroxides with rich vacancies and poly‐/low‐crystalline features are in situ generated through dissolution‐redeposition, and serve as the OER‐active species. The optimized Fe0.052 Ni‐POMo array pre‐catalyst has excellent activity and sustains ultrastable catalysis for 545 h. The complete reconstruction of POMo enables high catalytic durability (230 h) and stable active phase under realistic conditions (30 wt% KOH, 60.9 °C). Accordingly, the completely reconstructed catalysts with unique structures and ultrastable catalysis have the potential to be applied in industry. Abstract : Novel polyoxomolybdate‐organic complex oxygen‐evolving pre‐catalysts are introduced via a wet‐chemistry synthesis with fixed coordination chemistry. Their porosity and low crystallization promote diffusion‐leaching processes of the ligand and anion during the alkaline oxygen evolution reaction, resulting in radical phase reconstruction and in situ generation of nickel‐iron (oxy)hydroxides with rich defects. High durability and a stable active phase of the completely reconstructed catalyst under realistic conditions are achieved.